Gendered Reflections? Extremism in the UK’s Radical Right and al-Muhajiroun Networks - Elizabeth Pearson (Studies in Conflict & Terrorism, 2020)
The rise of populism and the radical right alongside ongoing global recruitment by jihadist groups has seen academics and popular discourse alike note parallels between the two. In particular, authors have emphasized gendered similarities between the movements. Based on ‘close-up’ ethnographic research, this article empirically shows how gender produces group members’ activism in two extreme movements: a network linked to the UK’s banned Islamist group al-Muhajiroun; and activists for the English Defence League, Britain First and other anti-Islam(ist) groups. Through a gendered analysis, the article problematizes assertions that the two movements mirror one another. In particular, it emphasizes the ways in which gender produces fragmentation across the anti-Islam(ist) movement, contrasted with a more consistent gendered logic in those networked to al-Muhajiroun. Its key contribution is to use ethnographic research to evidence the ways in which group members’ gendered activism ultimately undercuts group ideals.